Status of Household Solid Waste and People’s Perception on its Management at Sitakunda Upazila, Chittagong - Rana, Md. Juwel; Alam, Ohidul; Majumder, Sahadeb Chandra; Misbahuzzaman, Khaled (International Journal of Environment, 2017)
Urban household solid waste (HSW) is well-known, but has little knowledge about the rural areas and sub-cities. The quest of the study was to investigate current HSW management system and people’s attitude towards it’s at Sitakunda Upazila. The study was conducted through a semi-structured questionnaire survey by interviewing 150 households from 3 different socioeconomic groups. The results showed that on an average each household generated 1.26 kg/day wastes which stands at 0.24 kg/person/day in the study area. However, HSW generation is positively correlated with family size (rxy=0.991, p˂0.05), average age of family members (rxy=0.455, p˂0.01), and monthly earnings (rxy=0.999, p˂0.01) of the households. Amidst the various categories of wastes, vegetable and food wastes (VFWs) were identified as the highest value 68.4%. In contrast, 24.6% of the generated wastes were recyclable and 75.4% non-recyclable; 82.1% organic and 17.9% inorganic. A large percentage of sampled households opined that present HSW management involves merely partial collection that is also irregular in urban areas but absent in rural areas. Unfair HSW collection was noticed by 58.7% and partial source segregation is also rare 14%. Besides, 42.7% people were found to dispose their daily generated wastes by open dumping and 25.3% nearby lagoon. A large number of people were dissatisfied 68% and only 6.7% were satisfied with the existing HSW management system. In addition, most of the people encountered bad odor problems by 28.7% and wastes spread on roadside by 38%. Significant quantity of recyclable wastes was noticed to collect from households by hawkers/scraps in the study area and very few household were found to use VFWs with cow-dung to generate biogas.INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 58-75